Failure rates and factors associated with infrazygomatic crestal orthodontic implants - A prospective study - Gauri Gill; Keerthan Shashidhar; M.N. Kuttappa; Dhyan Kushalappa P B; Gautham Sivamurthy; Soham Mallick (Journal of Oral Biology and Craniofacial Research, 2023)
Objective: Infrazygomatic crestal (IZC) implants have gained increased popularity over the past few years. Hardly any studies have been done to assess the rate and reasons for failure of IZCs. This prospective study was planned and designed with the primary objective of assessing the rate of failure of bone-screws (BS) placed in the infrazygomatic crest. In continuation, the secondary objective was to assess the factors that were associated with the failure. Materials and methods: The study was carried out by taking a detailed case history, (age, gender, vertical skeletal pattern, medical history), photographic records, radiographs, and clinical examination of a total of 32 randomly selected. patients of south indian origin who required infrazygomatic implants bilaterally as the choice of anchorage conservation to retract their incisors. All selected subjects were required to take a PA Cephalogram after the implant placement. The age of the patients ranged from 18 to 33 with an average age of 25 years. The patient log was maintained which included the treatment mechanics, status of oral hygiene, stability of implants, time of loading of the implant, presence of inflammation and time of failure of implant. The angulation of implant was measured on a digital PA cephalogram using Nemoceph software. These parameters were examined to evaluate independent and dependent variables using the Chi-Square test and Fischer's exact test. Result: A failure rate 28.1% for IZC placed in the infrazygomatic crest region was observed. Patients with a high mandibular plane angle, poor oral hygiene, immediately loaded implant, peri-implantitis, and severe clinical mobility showed higher failure rates. Variables such as age, gender, sagittal skeletal pattern, length of the implant, type of movement, occluso-gingival position, method of force application, and angle of placement were not significantly associated with implant failure. Conclusion: Oral hygiene and peri-screw inflammation must be controlled to minimize the failure of bone screws placed in the infrazygomatic crest region. Loading of the implant should be done after a latent period of two weeks. A higher failure rate was observed in patients with vertical growth pattern.